2022
DOI: 10.1002/prop.202200019
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Hotspots: Mean Fields, Open EFTs, Nonlocality and Decoherence Near Black Holes

Abstract: Effective theories describing black hole exteriors resemble open quantum systems inasmuch as many unmeasurable degrees of freedom beyond the horizon interact with those we can see. A solvable Caldeira-Leggett type model of a quantum field that mixes with many unmeasured thermal degrees of freedom on a shared surface was proposed in arXiv:2106.09854 to provide a benchmark against which more complete black hole calculations might be compared. We here use this model to test two types of field-theoretic approximat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 133 publications
(113 reference statements)
0
13
0
2
Order By: Relevance
“…It was with the view to providing one of these benchmarks that reference [17] proposed a solvable Caldeira-Leggett style [18,19] model consisting of an external massless quantum field φ interacting with many unseen gapless thermal fields in a very small spatial volume (called a 'hotspot'). Some implications of this model, such as for the coherence of the state of the field φ, are explored in a companion paper [20].…”
Section: Introduction and Discussion Of Resultsmentioning
confidence: 99%

Qubit Heating Near a Hotspot

Kaplanek,
Burgess,
Holman
2021
Preprint
Self Cite
“…It was with the view to providing one of these benchmarks that reference [17] proposed a solvable Caldeira-Leggett style [18,19] model consisting of an external massless quantum field φ interacting with many unseen gapless thermal fields in a very small spatial volume (called a 'hotspot'). Some implications of this model, such as for the coherence of the state of the field φ, are explored in a companion paper [20].…”
Section: Introduction and Discussion Of Resultsmentioning
confidence: 99%

Qubit Heating Near a Hotspot

Kaplanek,
Burgess,
Holman
2021
Preprint
Self Cite
“…There are several directions in which this model might fruitfully be explored. In a companion work [43], we apply to it several approximate Open-EFT techniques designed to probe late-time evolution, to better identify their domains of validity and whether they can illuminate the extent to which the open nature of the hotspot causes a breakdown of local descriptions of the physics of the field φ living in R + . A second companion [44] explores the behaviour of an Unruh detector (or qubit) that couples to the field φ in the vicinity of the hotspot, to determine the extent to which it thermalizes as a function of its couplings and its distance from the hotspot.…”
Section: Discussionmentioning
confidence: 99%
“…Note however that the full correlation function W β = S + E β is not explicitly thermal since the temperature-independent contribution S obviously fails to satisfy a KMS-like condition analogous to (D.63). However, in a limit where E β dominates over S (provided t > |x| and t > |x |) one should expect to see thermality manifest itself more directly (this is explored using an Unruh-Dewitt detector model in [43], where it is shown that a stationary qubit outside the hotspot thermalizes whilst only interacting with φ).…”
Section: D23 Kms-like Condition For E βmentioning
confidence: 99%
See 2 more Smart Citations